Environmental policy and social solidarity: The problems of interconnection - Bikmetov Evgeniy; Frolova Irina; Lukmanova Raushaniya; Frolov Konstantin; Saitbattalov Iskander (BIO Web of Conferences)
The objective of the study is twofold: firstly, to develop an ESG strategy and secondly, to implement it as a solution to global environmental problems, based on the principles of solidarity of all participants at the international level. In the study, the authors employed three methodological grounds: firstly, systematicity and additionality, which were used to analyze multilateral interdependencies and fundamental contradictions that prevent the dominance of the principles of environmental policy and ESG-governance; secondly, the substantive analysis which serves as the foundation for comprehending the interconnections between socio-economic systems and the pivotal elements that shape their evolution within the context of the environmental agenda; thirdly, the logical analysis that enables the utilization of a diverse array of data obtained through the generalization of environmental policy and ESG governance. The study is grounded in the theoretical frameworks of the public sphere research and structural functionalism. The authors' conclusions are based on empirical data obtained during the implementation of the strategic project, “ESG models for the growth of new ecoterritories,” at the Ufa University of Science and Technology (Ufa, Russia). It may be concluded, therefore, that an ESG strategy aimed at social integration serves to unify the social organism and facilitate sustainable socio-economic development, while simultaneously fostering a system of values and a mode of thought characterised by solidarity. The paper justifies the proposed strategies for enhancing environmental quality. These include a focus on human-centric economic practices and the promotion of solidarity as a global and interhuman prosocial behavior.